Network Security System Design Using Firewall And VLAN Segmentation Based On Mikrotik At PT Global Solusindo Kompudata - Ari Ariyanto; Ade Setiawan (International Journal of Health Engineering and Technology, 2026)
PT Global Solusindo Kompudata's simple network infrastructure is vulnerable to unauthorized access and decreased productivity due to the lack of VLAN segmentation and firewall. This study aims to design a network security system using VLAN and Layer-7 firewall based on MikroTik for traffic isolation and access restrictions on unproductive sites. This type of development research (R&D) with a mixed methods approach using GNS3 simulation. The population of the entire new building network (93 devices); purposive samples of MikroTik routers, Cisco switches, and specific VLANs. Winbox, GNS3, and Layer 7 analyzer instruments; qualitative-quantitative descriptive analysis with triangulation. The results show that VLAN 10-40 isolates inter-segment communication and the firewall blocks YouTube on VLAN 20-30, with CPU utilization dropping by 30-40%. The design is effective for SMEs, physical implementation with advanced QoS testing is recommended.